2018
DOI: 10.1177/0160449x18767749
|View full text |Cite
|
Sign up to set email alerts
|

Pay, Power, and Health: HRI and the Agricultural Conundrum

Abstract: As part of a five-year integrated study on heat-related illness (HRI) among farmworkers in California, the California Institute for Rural Studies (CIRS) convened focus groups with farmworkers in regions of the state where HRI was prevalent. CIRS also interviewed employers and other stakeholders in the state. While this study was not designed to identify causal relationships, we were able to identify patterns of interaction that point to the intersection of agricultural system structures and worker agency in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Piece rate compensation is another factor that makes agricultural workers vulnerable to heat stress because it pushes workers to forgo rest breaks in the effort to maximize the amount of daily compensation, as was voiced by piece-rate workers in our study. This observation is consistent with other studies (Faucett et al, 2007;Holmes, 2013;Wadsworth et al, 2019). Employers, however, frame piece rate compensation as a system that provides workers with autonomy to pace themselves, take breaks as needed, and start and stop work at any time (Wadsworth et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Piece rate compensation is another factor that makes agricultural workers vulnerable to heat stress because it pushes workers to forgo rest breaks in the effort to maximize the amount of daily compensation, as was voiced by piece-rate workers in our study. This observation is consistent with other studies (Faucett et al, 2007;Holmes, 2013;Wadsworth et al, 2019). Employers, however, frame piece rate compensation as a system that provides workers with autonomy to pace themselves, take breaks as needed, and start and stop work at any time (Wadsworth et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Focus groups with farmworkers in South Carolina and California highlighted that workers feel pressure to work faster for longer hours and take fewer breaks when they are paid piece rate, and that this can increase HRI risk. 42,45 Studies in California and Washington showed that workers paid piece rate, relative to those paid hourly or salary, had higher physical activity levels, 43 higher core body temperature readings, 44 higher levels of acute kidney injury, 21 and higher odds of HRI symptoms. 46 Our findings could demonstrate that child workers feel less financial pressure to maximize earnings by working at a dangerous pace in the heat than their adult counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…37 Many farmworkers are paid piece rate wages, which incentivizes productivity and can make workers less likely to take breaks and more likely to work at an unsafe pace. [42][43][44][45][46] Previous research with Latinx child farmworkers in North Carolina found that they perceived low levels of work safety culture and climate in farm work. 47,48 Figure 1.…”
Section: Child Farmworkers and Exposure To Heatmentioning
confidence: 99%
“…There appears to be an inverse relationship between the observed metabolic rate and ambient temperature, suggesting there is decreased activity when temperatures increase and increased activity when temperatures decrease. The intense work pace observed in March may also be a result of how the workers are paid [28,29]. March workers reported being paid by the completion of a row of vines rather than by a set time frame (i.e., hourly, daily, or monthly).…”
Section: Heat Stressmentioning
confidence: 99%
“…Recent work has emphasized the deleterious effects heat exposure can have on workers from a productivity standpoint, with reduced productivity as heat exposure increases [3,11,[24][25][26][27]. Furthermore, agricultural workers frequently make self-care decisions based on the perception of productivity losses or gains, resulting in higher rates of heat-related injuries when paid by the pound, piece, or line of work completed in the field [28][29][30]. Heat strain can be prevented with adequate fluid intake, sufficient resting periods in shaded areas, adequate time for recovery in cooler areas, the introduction of increased convective and evaporative cooling, and appropriate clothing such as nanoporous metalized polyethylene textiles or cooling vests [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%